Zróżnicowanie rozwoju regionalnego na poziomie NUTS-2 w krajach Unii Europejskiej - Strahl, Danuta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The article presents an assessment of the level of diversification of regional development at NUTS-2 level in the 25 countries of enlarged Europe. The analysis covers 252 regions and takes into account five characteristics of regional development:- regional unemployment rate in %,- Gross Domestic Product per capita (GDP pc) in the region (acc. to PPS - Purchasing Power Standard),- increase rate of regional GDP pc in the years 2001-2000,- total GDP produced in the region (in millions of PPS),- region's population size.The inner diversification of regions within the 25 European countries is described with two statistical measures:- variance index, and- variable range as a relationship between extreme values of a variable. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 17-26